Optimizing in-season strength and power development in high-level handball players: comparing heavy strength training versus combined strength- and power training - Vårvik, F. T.; Raastad, T.; Torstveit, M. K.; Ruiven, M. V.; Guddal, M.; Kristiansen, S.; Aarrestad, S.; Lund, A. B.; Bjørnsen, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Handball players often combine strength and power training for additive performance benefits. However, in-season handball-specific training and matches include high-intensity actions questioning the benefit of adding power training in this period. Hence, the aim of this study was to compare the effect of high-load versus combined high-load and power training on strength and power capacities during the competitive season in handball players. METHODS: Twenty-nine (11 males) high-level handball players were randomized into high-load strength training (HL; n=15, 20±3 years) and combined high-load and power training (COM; n=14, 22±3 years). Training sessions were conducted twice weekly for 15 weeks, with weekly supervision. Per week, the HL group completed 5-9 sets per muscle group (80-85% one-rep max [RM]), and the COM completed 2-4 high-load sets, 56-66 bodyweight jumps, and 4-7 sets of power exercises (*50% 1RM). Outcomes pre- and post-intervention included 1RM squat and bench press, maximal isometric strength (MVC) and rate of force development (RFD; 0-30, -50, -100, and -250ms time intervals), pneumatic resistance leg press maximal power (Pmax), countermovement jump (CMJ) height and power; 10- and 30m linear sprint and change of direction (CoD) times (4x180 turns). Subjective readiness was rated using a 5-point Likert scale before all matches. The data were analyzed with t-tests and are reported as mean change with 95% confidence intervals or standard deviations. RESULTS: Over 15 weeks, players engaged in ~one match and four handball training sessions per week. Training attendance was 87±11% in the HL group and 84±13% in the COM group. MVC and CMJ power increased 6.6% (1.2, 12.1, p